PENGEMBANGAN HANDOUT BERBASIS GAMBAR DISERTAI PETA KONSEP PADA MATERI SISTEM GERAK PADA MANUSIAUNTUK TINGKAT SMP - Revi Oktarina, Sri Maria; Ardi, Ardi; Nerita, Siska (Pendidikan Biologi, 2013)
ABSTRAKTeaching materials that are less attractive and it is not yet appropriate with the studentâs need will disturb the teaching of biology. The purposes of this study was to produce a valid and practical handout, based on image with a concept map on the motion system in humans for junior high school student. The another purpose was to determine the feasibility stage of development of handout based on image with a concept map in accordance with the level of education curriculum unit. This research was the development research of procedural models comprising the steps of defines, designs, and develops. This studied conducted at SMPN 1 Kubung class VIII for second semester of academic years 2012/2013. The data was collected by questionnaire instrument. Analytical techniques used were qualitative and quantitative analysis for the feasibility study handout based on image with a concept map on human motion system.Based on the research that has been done, it can be concluded that the media handout based on image with a map concept on material of human motion system for SMP had valid and practical criteria.Â Â Â